Engaging with cultural practices in ways that benefit women in northern Nigeria - Tipilda, A.; Alene, A.; Manyong, Victor M. (Informa UK Limited, 2008)
This study explores the intra-household impact of improved dual-purpose cowpea (IDPC) from a gender perspective, in terms of productivity and food, fodder, and income availability, the impact of which is linked to the income thus placed in the women’s hands. Surplus income is important in providing food and nutritional benefits to the home, particularly during periods of risk. More importantly, income generated through the adoption of improved cowpea varieties has entered a largely female domain, where transfers of income reserves were passed on between women of different ages, with significant impact in terms of social and economic development. However, the technology has strengthened the separation of working spheres between men and women. Future technologies should, from the outset, explore provisions existing within the local rubric, to focus on women with the aim of expanding their participation in agriculture with the associated benefits to their families.